Desvios de linguagem: as contribuições de Rubens Gerchman e Nelson Leirner para a prática da apropriação de imagens na arte contemporânea no Brasil - Silva, Vitor Marcelino da (2012)
This dissertation aims to analyze the contributions of Brazilian artists Rubens Gerchman and Nelson Leirner for the recurrent practice of image appropriation in contemporary art in Brazil. To do so, first we tried to define some important concepts and to resume a concise history of image appropriation to become clear what are the relations, notes, and trials that provided to both artists before history of this practice. To analyze all production of artists in which we perceive the appropriation of images was also very important to be perceived more clearly the actual contributions. In this production, which then extended from the 1960 s to the 1990 s, were chosen a work and a series that proved significant in this process and therefore had a analysis more timely: the work Lindonéia a Gioconda do subúrbio, produced by Rubens Gerchman in 1966 and the series Homenagem a Fontana, produced by Nelson Leirner in 1967 which consists of three works, Homenagem a Fontana I, II and III. The chosen works were extremely relevant to the research objective was achieved and summarizes important issues of all appropriationist production of the artists. The period extremely close to the production of works led to examine more thoroughly the second half of the 1960 s where we find a consistent theoretical and artistic production that proved entirely suitable for the practice of appropriating images to arise. It is then from the perception of the artistic context not only Brazil but also internationally it was possible to realize the important contributions of these works.